(untitled) (Ciudades, 2017)
The article examines the international influences and relationships for the urban and architectural design of the Spanish colonization villages. References ranging from the debate on land use and settlement patterns to the specific to the urban layout and its interactions with its architecture; both from the understanding of theories and urban schemes to the copy of laws; imported models as the American neighborhood unit or the Radburn schema, the Israelian Territorial Plan, the Italian consideration of historical and cultural conditioning, etc. including settlement patterns tested in the republican Spain. Also, from an urban planning perspective, it examines the meaning of the answers or solutions given in these villages to the needs of space, housing, leisure and social organization of life.